JointSearch: Efficient parametric detailing preparation through user-defined and property-based joint type filtering. (September 2021) - Haddal Mork, John; Luczkowski, Marcin
Detailing joints are important when designing structures. In this design process, a structure is divided into different joint types. Digital fabrication and algorithmic aided design have changed the conceptions and requirements of joint detailing. However, parametric tools that can efficiently identify joint types based on the solution space are not available. This article presents a methodology that efficiently generates topological relations and enables the user to assign joint instances to joint types. A series of property-based search criteria components is applied to define the solution space of a joint type. Valid joints are coherently filtered, deconstructed and outputted for detailing. The article explains both the methodology and programming-related aspects of the joint type filtering. The article concludes that the developed methodology offers the desired flexibility and may be suitable for other materials and applications.